Defence in a democracy. A church perspective on the post-apartheid defence review process. - Koopman, NN (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
This article consecutively outlines the Defence Review Process in South Africa since the dawn of democracy a decade ago, the consequent policies, actions and involvement in arms deals of our government and the responses of South African churches. The second section entails a theological evaluation of the responses of the churches. The overall conclusion is that churches succeeded to a high degree to engage with this public challenge in modes that are appropriate for public theology in the context of a democracy. In a last section some suggestions are made with regard to the future role of churches. This entails a more inclusive understanding of the church and a more comprehensive understanding of security.